(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: Identify factors associated with gestational diabetes mellitus (GDM) among pregnant women undergoing oral glucose tolerance testing (OGTT) at A Thai Nguyen Hospital from October 2024 to April 2025. Subjects and research methods: A prospective cross-sectional study was conducted on 332 pregnant women who underwent oral glucose tolerance testing at A Thai Nguyen Hospital, from October 2024 to April 2025. Results: The prevalence of GDM in the study population was 34,9%. Factors associated with GDM included maternal age ≥35 years (p = 0,030; OR = 1,980; CI95%: 1,060-3,690), history of miscarriage and early intrauterine fetal demise (p = 0,031; OR = 1,881; 95%CI = 1,055-3,353), history of GDM (p = 0,000; OR = 3,000; 95%CI = 2,572-3,499), history of macrosomia (p = 0,000; OR = 3,964; 95%CI = 1,969-7,978), first-degree family history of diabetes (p = 0,000; OR = 12,802; 95%CI = 4,777-34,312), first-degree family history of hypertension (p = 0,000; OR = 2,711; 95%CI = 1,593-4,613), assisted reproductive technology (p = 0,035; OR = 2,331; 95%CI = 1,042-5,236), and parity ≥2 (p = 0,032; OR = 1,681; 95%CI = 1,043-2,710). Conclusion: The prevalence of GDM was 34,9%. There was an association between GDM and maternal age, history of miscarriage and early intrauterine fetal demise, history of GDM, history of macrosomia, family history of diabetes, family history of hypertension, mode of conception, and gravidity.